Linking chemistry with physics: Arguments and counterarguments - Lombardi, Olimpia Iris (2014)
The many-faced relationship between chemistry and physics is one of the most discussed topics in the philosophy of chemistry. In his recent book Reducing Chemistry to Physics. Limits, Models, Consequences, Hinne Hettema (Reducing chemistry to physics. Limits, models, consequences, Rijksuniversiteit Groningen, Groningen, 2012) conceives this relationship as a reduction link, and devotes his work to defend this position on the basis of a “naturalized” concept of reduction. In the present paper I critically review three kinds of issues stemming from Hettema’s argumentation: philosophical, scientific and methodological.